The Influence of Brand Trust and Product Quality on Customer Loyalty Through Customer Engagement on Users Toyota Cars in Medan City - Indawati Lestari; Isfenti Sadalia; Endang Sulistya Rini; Beby Karina Fawzeea Sembiring (Universitas 17 Agustus 1945 Semarang, 2023)
The purpose of this study was to determine and analyze the effect of brand trust and product quality on customer loyalty through customer engagement with Toyota car users in Medan City. The research was conducted on Toyota car users in Medan City. The population of all Toyota brand car users in Medan City. Samples were taken using the Slovin formula of 150 respondents. Data analysis was performed using path analysis in the SPSS program. The results of the sub-1 analysis prove that brand trust and product quality have a positive and significant effect on customer engagement. The results of the sub-2 analysis prove that brand trust and product quality have a positive and significant effect on customer loyalty through customer engagement.